American pie - Biggs, Jason, 1978-; Klein, Chris, 1979-; Lyonne, Natasha; Nicholas, Thomas Ian.; Reid, Tara, 1975-; Suvari, Mena, 1979-; Levy, Eugene; Zide, Warren; Perry, Craig; Moore, Chris; Weitz, Chris, 1969-; Weitz, Paul, 1966-; et al. (Universal City, CA : Universal, 1999)
Follows the hapless adventures of four "unlucky in love" high school friends as they gear up for the prom.
Producer, Warren Zide, Craig Perry, Chris Moore, Chris Weitz ; director, Paul Weitz ; writer, Adam Herz ; music, David Lawrence.
Jason Biggs, Chris Klein, Natasha Lyonne, Thomas Ian Nicholas, Tara Reid, Mena Suvari, Eugene Levy.
DVD format.
In English and French with English and Spanish language subtitles.
Keywords: High school students -- Drama; Proms -- Drama; Feature films; Video recordings for the hearing impaired